Copreneurial couples in startups: A comprehensive analysis of copreneurial couples in startups compared to classical businesses - Eliza Alena Marie Weitzel (Junior Management Science (JUMS), 2025)
Due to a lack of attention in research to draw a connection between couple businesses and their existence as a form of startup teams, this paper aims to provide deeper insights into the structure and behavior of copreneurial couples in startups. This lack needs to be addressed due to the increase of these phenomena and possible outcomes for the startup world, as copreneurial couples in startups tend to be viewed as red flags without proof of this being valid. For this purpose, a qualitative, theory building research approach was chosen, in which copreneurial couples of startups and classical businesses were interviewed. As a result, a comprehensive model of the development dynamics of copreneurial couples and a hands-on framework were created. The main finding is limited differences between copreneurial couples in startups and classical businesses regarding motivations, processes, challenges, and opportunities when combining work and private life. The primary differentiation lies in the amount of workload, the variation in the procurement of external financial resources, and the environment they are navigating in. The work confirms parts of the previous literature but also provides new insights into communication, work-life balance, decision-making processes, and external influences. Finally, the framework can be used by copreneurial couples to structure, prioritize, and navigate the challenge of wholly combining their work and private domain.
Keywords: 650; copreneurial couples; copreneurship; couple business; startups; team dynamics